PAINLESS “HUNGER-DEATH” IS A MYTH - Ginneken, V.J.T. Van (Acta Scientiae et Intellectus, 2024)
Since at present A.D. 2015 around one billion people are exposed to hunger (< 200 kcal/caput/day) -among them around 7 million children (aged < 5 years) and around 4 million neonatal deaths- we will discuss the important question “Do we have pain during starvation resulting in a hunger death?” Because of the total physiological and biochemical degeneration during a hunger death, we can assume it will be accompanied with tremendous pain which can be relieved by treatment anodyne medicine like morphine, which are not available for these one billion people in the underdeveloped world. When agriculturist don’t succeed to meet the feeding demands of the ≈ 10 billion people who will life at planet Earth at the midst of this century a tremendous disaster and hunger pandemic will strike planet Earth. Food is so integral to human wellbeing and there is such a close relation between energy, food, nutritional quality and health on a global scale at our planet that it not only opens the discussion about the ethics that at present on a global scale the neglected ≈one billion people are dying a cruel hunger death, but also suggest a smart innovative perspectives “to ban the hunger”, and over a period of three decades gradually make the transition gradually from a fossil energy driven economy towards a seaweed based economy meeting the 8 millenium goals.